Science for environmental protection : the road ahead - National Research Council (U.S.). Committee on Science for EPA's Future; National Research Council (U.S.). Division on Earth and Life Studies; National Research Council (U.S.). Board on Environmental Studies and Toxicology (Washington, D.C. : National Academies Press, 2012)
"In anticipation of future environmental science and engineering challenges and technologic advances, EPA asked the National Research Council (NRC) to assess the overall capabilities of the agency to develop, obtain, and use the best available scientific and technologic information and tools to meet persistent, emerging, and future mission challenges and opportunities. Although the committee cannot predict with certainty what new environmental problems EPA will face in the next 10 years or more, it worked to identify some of the common drivers and common characteristics of problems that are likely to occur. Tensions inherent to the structure of EPA's work contribute to the current and persistent challenges faced by the agency, and meeting those challenges will require development of leading-edge scientific methods, tools, and technologies, and a more deliberate approach to systems thinking and interdisciplinary science. Science for Environmental Protection: The Road Ahead outlines a framework for building science for environmental protection in the 21st century and identified key areas where enhanced leadership and capacity can strengthen the agency's abilities to address current and emerging environmental challenges as well as take advantage of new tools and technologies to address them. The foundation of EPA science is strong, but the agency needs to continue to address numerous present and future challenges if it is to maintain its science leadership and meet its expanding mandates"--Publisher's description.
Summary -- Introduction -- Challenges of the 21st century -- Using emerging science and technologies to address persistent and future environmental challenges -- Building science for environmental protection in the 21st century -- Enhanced scientific leadership and capacity in the U.S. Environmental Protection Agency -- Findings and recommendations -- [Appendixes].
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United States. -- Environmental Protection Agency; United States. -- Environmental Protection Agency; Environmental sciences -- United States; Environmental sciences -- Research -- United States; Environmental protection -- Research -- United States; Environmental protection -- United States; Environmental protection -- Decision making; Environmental policy -- United States; Sciences de l'environnement -- États-Unis.; Sciences de l'environnement -- Recherche -- États-Unis.; Environnement -- Politique gouvernementale -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Environmental policy; Environmental protection; Environmental protection -- Decision making; Environmental protection -- Research; Environmental sciences; Environmental sciences -- Research; United States